1968
DOI: 10.1084/jem.128.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Induction of Tolerance of the H-Y Antigen in Mice With Neonatal Skin Grafts

Abstract: In contrast to the uniform rejection of adult male skin isografts by C57BL/6 females, neonatal male skin isografts are frequently accepted. Moreover, 50% of all females which accept a neonatal male skin graft for 50 days accept a subsequent adult male skin graft as well. This ability of neonatal skin to produce tolerance has been investigated under a variety of experimental conditions. The results indicate: (a) Even when a newborn male skin graft is transplanted concomitantly with an adult graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

1972
1972
1986
1986

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…Whereas B6 female mice uniformly reject H-Y-incompatible adult male skin isografts [their median survival time (MST) is about 20 days], neonatal male skin isografts often are accepted (12). Moreover, such newborn grafts frequently render their hosts unresponsive to adult male skin, especially ifthey precede the latter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas B6 female mice uniformly reject H-Y-incompatible adult male skin isografts [their median survival time (MST) is about 20 days], neonatal male skin isografts often are accepted (12). Moreover, such newborn grafts frequently render their hosts unresponsive to adult male skin, especially ifthey precede the latter.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the rat experiment are being published elsewhere (11), and most of the data concerning H-Y-incompatible grafts originate from a previous study (12). Thus, although what follows will include data from all of these studies, only the experiments involving Skn will be described in detail.…”
mentioning
confidence: 99%
“…It has been shown that neonatal donor skin trans planted to adult mice displays extended survival when compared to adult donor skin [1][2][3][4], Previously, our laboratory has demonstrated the superiority of using neonatal donor tissue rather than adult tissue in the murine skin allograft model [5], We showed when neonatal (24 h old) C3H/He skin was grafted to anti-lymphocyte (ALS)-treated B6AF1 adult recipients, the resulting median survival time was greater (48 days) than when adult skin was trans planted (24 days).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when H-2 compatibility exists, such transplants may survive indefinitely, in many cases abrogating their hosts' capacity to reject subsequent adult tissues bearing the same transplantation antigens (1,2,7). For example, C57BL/6 female mice regularly reject H -Yincompatible skin isografts from adult males (median survival time, 24.5 days), but a~6 (74%) accept those from newborn males (8). Of those females which tolerate neonatal male grafts, half are unresponsive to subsequent adult male grafts as well (8).…”
mentioning
confidence: 99%
“…For example, C57BL/6 female mice regularly reject H -Yincompatible skin isografts from adult males (median survival time, 24.5 days), but a~6 (74%) accept those from newborn males (8). Of those females which tolerate neonatal male grafts, half are unresponsive to subsequent adult male grafts as well (8).…”
mentioning
confidence: 99%